Effects of Evening Exposure to Light from Organic Light-Emitting Diodes on Melatonin and Sleep - Park, Hea Ree; Choi, Su Jung; Jo, Hyunjin; Cho, Jae Wook; Joo, Eun Yeon (Journal of clinical neurology (Seoul, Korea), 2020)
Organic light-emitting diodes (OLEDs) emit less blue light than traditional light-emitting diodes (LEDs), but the effects of OLED light exposure (LE) on melatonin and sleep have not been evaluated.BACKGROUND AND PURPOSEOrganic light-emitting diodes (OLEDs) emit less blue light than traditional light-emitting diodes (LEDs), but the effects of OLED light exposure (LE) on melatonin and sleep have not been evaluated.Twenty-four healthy subjects (age 26.9±5.7 years; including 18 females) with the intermediate chronotype were exposed to three different light conditions [4,000 K 150 lux OLED LE, 4,000 K 150 lux LED LE, and dim light (DL) at <10 lux] for 6.5 h from 17:30 to 24:00, in a random order and with a 1-week interval. Participants entered the unit for the experiment at 16:00, and their daylight was measured by actigraphy from 8:00 to 16:00 during each session. Saliva samples for melatonin were taken every hour from 18:00 to 24:00. Sleep was monitored by polysomnography, and vigilance was evaluated by psychomotor vigilance test upon awakening.METHODSTwenty-four healthy subjects (age 26.9±5.7 years; including 18 females) with the intermediate chronotype were exposed to three different light conditions [4,000 K 150 lux OLED LE, 4,000 K 150 lux LED LE, and dim light (DL) at <10 lux] for 6.5 h from 17:30 to 24:00, in a random order and with a 1-week interval. Participants entered the unit for the experiment at 16:00, and their daylight was measured by actigraphy from 8:00 to 16:00 during each session. Saliva samples for melatonin were taken every hour from 18:00 to 24:00. Sleep was monitored by polysomnography, and vigilance was evaluated by psychomotor vigilance test upon awakening.Melatonin onset occurred at 21:11±01:24, 21:20±01:19, and 21:36±01:16 in the DL, OLED, and LED conditions, respectively. Melatonin onset was significantly delayed under LED LE compared to DL (p=0.007) but did not differ under OLED LE (p=0.245). Melatonin suppression, sleep parameters, and vigilance were similar among the three light conditions. The accumulated amount of daytime light in each session was negatively correlated with the melatonin onset time under the DL (rho=-0.634, p=0.002) and OLED (rho=-0.447, p=0.029) conditions, not under the LED condition (p=0.129).RESULTSMelatonin onset occurred at 21:11±01:24, 21:20±01:19, and 21:36±01:16 in the DL, OLED, and LED conditions, respectively. Melatonin onset was significantly delayed under LED LE compared to DL (p=0.007) but did not differ under OLED LE (p=0.245). Melatonin suppression, sleep parameters, and vigilance were similar among the three light conditions. The accumulated amount of daytime light in each session was negatively correlated with the melatonin onset time under the DL (rho=-0.634, p=0.002) and OLED (rho=-0.447, p=0.029) conditions, not under the LED condition (p=0.129).Melatonin onset under OLED LE was not significantly delayed compared to DL. Exposure to sufficient daylight may advance melatonin onset even when a subject is exposed to OLED LE in the evening.CONCLUSIONSMelatonin onset under OLED LE was not significantly delayed compared to DL. Exposure to sufficient daylight may advance melatonin onset even when a subject is exposed to OLED LE in the evening.